Obesity (Sthaulya) Prevention with Yoga – A Literary Review - Mishra, Akash; Bhambu, Sudesh Kumar; Rao, Archna (International Research Journal of Ayurveda & Yoga, 2025)
Due to the rapid modernization in the present era, sedentary lifestyle, and abundance of nutrition, non-communicable diseases have increased tremendously and are now becoming the chief cause of obesity all over the world. Obesity is a lifestyle disorder affecting both developing and developed countries. Obesity (Sthaulya) is vastly increasing due to the changes in the Aahara, Vihara, and Manasikaawastha of mankind. Obesity is a disorder characterized by increased body weight and excessive fat deposition in the body. The root causes, such as overconsumption of calories and reduced physical activity, lead to serious health complications such as diabetes, cardiovascular disease, and arthritis. This reduces the average life span and decreases the quality of life. In Ayurveda, Sthaulya (obesity) is a condition where aggravation of Doshas will cause improper transformation of saar bhaga of aahara, resulting in more formation of Meda Dhatu and inappropriate nourishment of other Dhatus of the body. This article is to explore the impact of the Ayurvedic approach on obesity. To find out the causative factors behind obesity and available Ayurvedic Chikitsa with the help of Yoga. Embracing a balanced lifestyle, staying physically active, and managing emotional stress are key factors in effectively addressing and preventing obesity. Obesity has become a global health concern, increasing the risk of various diseases such as diabetes, heart and joint disorders. While diet and exercise play a crucial role in weight management, Yoga provides a holistic approach that not only helps in maintaining weight but also improves mental well-being and overall health. How Yoga Helps in Obesity Prevention:- Yoga is not just stretching and making the body flexible but also enhancing metabolism, strengthening muscles, improving digestion, and reducing stress, which are all essential for maintaining health. Unlike heavy workouts, Yoga is gentle on the body and can be practiced by people of all fitness levels.[1] Worldwide obesity prevalence has nearly doubled between 1990 and 2022. About 16% of the adult and elderly population were obese in 2022, which is nearly 890 million. Obesity is physiologically caused by an imbalance between food consumption and energy expenditure, leading to excessive accumulation of fat in the form of adipose tissue. There is an increase in the number and enlargement of adipose cells. Obesity